The A to Z of shamanism - Harvey, Graham, 1959-; Wallis, Robert J.; Harvey, Graham, 1959- (Lanham, Md. : Scarecrow Press, 2010)
Explores the common ground of shamanic traditions and evaluates the diversity of both traditional indigenous communities and individual Western seekers.
The hardback version of this book has title: Historical dictionary of shamanism, c2007.
Includes bibliographical references (p. 245-306)
Description based on print version record.
Keywords: Shamanism -- History -- Dictionaries; BODY, MIND & SPIRIT / Spirituality / Shamanism; Electronic books